2018
DOI: 10.1016/j.chest.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

CORK Study in Cystic Fibrosis

Abstract: Early and sustained improvements on ultra-low-dose CT scores suggest it may be a useful method of evaluating treatment response. It paralleled improvement in symptoms, circulating inflammatory markers, and changes in the lung microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 41 publications
1
32
2
Order By: Relevance
“…Furthermore, observational studies have demonstrated that ivacaftor improved pancreatic function and mucociliary clearance. Reduction in the levels of blood inflammatory biomarkers, and smooth muscle and lung structure abnormalities have also been observed (Adam et al, 2016;Hisert et al, 2017;Donaldson et al, 2018b;Ronan et al, 2018).…”
Section: Potentiators: Restoring the Channel Gating And Conductancementioning
confidence: 92%
“…Furthermore, observational studies have demonstrated that ivacaftor improved pancreatic function and mucociliary clearance. Reduction in the levels of blood inflammatory biomarkers, and smooth muscle and lung structure abnormalities have also been observed (Adam et al, 2016;Hisert et al, 2017;Donaldson et al, 2018b;Ronan et al, 2018).…”
Section: Potentiators: Restoring the Channel Gating And Conductancementioning
confidence: 92%
“…Here, we explore the complex role of streptococci in CF-associated airway infections ( Fig. 1), in particular, the observation that streptococci, in a species-dependent fashion, either may be associated with a lower disease burden than typical CF pathogens (2,9,12,21,29) or, alternatively, may contribute to pulmonary exacerbations (1,6,(17)(18)(19). We also review recent studies indicating that streptococci influence and can be influenced by other microbes in the context of a polymicrobial infection in patients with CF.…”
Section: )mentioning
confidence: 99%
“…The interaction of P. aeruginosa with S. pneumoniae has not been investigated in any In CF airways, an increased prevalence of Streptococcus spp. has been correlated with clinical stability, lower inflammation, and/or less severe outcomes (2,9,12,21,29), but it is unclear whether this is due to direct interactions with the airway epithelium, is due to interactions between the streptococci and the microbiome that lead to increased microbial diversity, or is a consequence of less damage to the airway. Oral streptococci have been demonstrated to inhibit P. aeruginosa growth through the production of hydrogen peroxide and reactive nitrogenous intermediates (49)(50)(51); by inhibiting P. aeruginosa, streptococci could open up niches for increased microbial diversity in the lung, which could aid clinical stability.…”
Section: Is There a Role For Typical Pathogenic Streptococci In Cf?mentioning
confidence: 99%
See 2 more Smart Citations